2021
DOI: 10.1590/1806-9282.20201088
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation: survival and indexes of donor-recipient matching

Abstract: OBJECTIVE:The aim of this study was to determine the prospective capacity and impact of donor risk index, preallocation survival outcomes following liver transplant, donor model for end-stage liver disease, and balance of risk on patients' 30-day survival after liver transplantation. METHODS:We prospectively analyzed patient survival in a multicentric observational cohort of adult liver transplantation through the year of 2019 at the state of Paraná, Brazil. The receiver operating characteristic curve, the are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
1
6
0
3
Order By: Relevance
“…"Even the best organ may fail when transplanted in a severely ill environment with marginal perfusion", 14(p.960) SOFT and BAR scores better predict graft-recipient interaction and post-operative mortality. 31 Given that, our findings demonstrated that the RA group was constituted by less severe patients stratified by BAR score (p = 0.0028), reassuring the notion of high risk organs to fewer sick patients. There was no difference in SOFT score (p = 0.0602), possibly because SOFT score includes recipients' characteristics (ascites, portal vein thrombosis, previous surgeries) that may raise the final score in the RA group.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…"Even the best organ may fail when transplanted in a severely ill environment with marginal perfusion", 14(p.960) SOFT and BAR scores better predict graft-recipient interaction and post-operative mortality. 31 Given that, our findings demonstrated that the RA group was constituted by less severe patients stratified by BAR score (p = 0.0028), reassuring the notion of high risk organs to fewer sick patients. There was no difference in SOFT score (p = 0.0602), possibly because SOFT score includes recipients' characteristics (ascites, portal vein thrombosis, previous surgeries) that may raise the final score in the RA group.…”
Section: Discussionsupporting
confidence: 63%
“…The literature brings the notion that livers from expanded criteria donors may be directed to candidates with low MELD scores 4,27,30 and in this cohort lower quality organs (RA group -higher DRI) were allocated to patients with lower MELD scores, finding already reported in literature. [3][4][5][6]11 Liver Transplantation in Rescue Allocation: Comparison of the Donor Risk Index, Balance of Risk Score and Graft Function After Liver Transplantation MELD is well known for its inability to predict post-operative mortality, 31 owing to a lack of fine tuning regarding the graftrecipient match. such as clinical conditions or operative factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A literatura traz a noção de que os fígados dos doadores de critérios expandidos podem ser dirigidos a candidatos com escores MELD baixos 4,27,30 e nesta coorte órgãos de qualidade inferior (grupo RA -DRI mais alta) foram alocados a pacientes com escores MELD mais baixos, achado já relatado na literatura. [3][4][5][6]11 MELD é bem conhecido por sua incapacidade de prever a mortalidade pós-operatória, 31 devido à falta de ajuste fino em relação à correspondência enxerto-recipiente. Tais como condições clínicas ou fatores cirúrgicos.…”
Section: Resultsunclassified
“…Further to this, the risk - benefit assessment must be individualized as not all perspective recipients present with the same risks, nor should they all be expected to glean the same benefits. Despite research into overall risk ( 10 , 11 ), the transplantability of each patient is largely subjective. Surgically high-risk recipients are those patients with certain factors that present additional obstacles, requiring the surgical team to adapt their strategy from that of a routine transplant.…”
Section: Introductionmentioning
confidence: 99%